Feminine Sensuality. - Alizade, Alcira (Karnac Books, 1999)
A passionately written and passion-arousing book that not only brings the male reader closer to the Eternal Feminine - the dark area so dreaded by Freud - but also gives women readers more trust in their feminine condition. 184 pages.